Large deforamation of thin-walled tubular structure - Ismail, Hina Muhammad (2013)
In automobile and aerospace industries, thin-walled tubular structures have been widely used as key components to improve energy absorption capacity under axial compressive loads, which play an important role in improving the vehicle crashworthiness without increasing body weight. In this project, low carbon steel has been used to study the effect of loading rate onto sheet metal. Metallurgical study carried out to identify microstructure, chemical composition and hardness test of low carbon steel. From tension test at 0.001/s strain rate, stress-strain curve develop to identify the mechanical properties. Johnson –Cook model technique is adopted and parameters of Johnson – Cook model (A, B, C, m and n) have been extracted and use in FE simulation. Strain gauge rosette inserted on the center of the tube to determine strain at specific points on the structure. Wood of 10mm inserted at the top and bottom of the tube to avoid localized buckling. Then, axial compression test has been conducted experimental and FE simulation to validate the results.